KAJIAN EKSPERIMENTAL PENGARUH PARAMETER OPERASI TERHADAP PEMECAHAN GELEMBUNG DAN KINERJA PEMBANGKIT GELEMBUNG MIKRO TIPE SWIRL - Mawarni, Drajat Indah; Budhijanto , Wiratni Budhijanto; Deendarlianto , Deendarlianto; Ristiyanto , Hartono Guntur Ristiyanto; Marahendra , Wawan Dedi Marahendra; Indarto , Indarto (Jurnal Rekayasa Mesin, 2024)
In this study, we present the bubble breaking mechanism of the rotating flow in the swirl type microbubble generator (MBG) on the resulting performance in this case the oxygen dissolution rate. This type of MBG is an aeration technology and has been developed in recent years by utilizing the turbulence of liquid fluid flow to produce micron-sized bubbles. The pressure difference created by changing the cross-sectional diameter causes air to be sucked in automatically in the mixing channel and forms a bubble channel before finally bursting to form micron-sized bubbles at the MBG outlet. The experiment was carried out in a transparent container measuring 2.8 m x 0.6 m x 0.6 m which was filled with water as high as 0.4 m. This study is focused on studying the mechanism of bubble breakdown at the MBG outlet on the dissolution rate of oxygen (dissolved oxygen/DO) which is influenced by the volumetric flow rate of liquid (Q_L) and volumetric flow rate of air (Q_G). Various combinations of Q_L and Q_G values were systematically compared with the resulting oxygen mass transfer coefficient (KLa) values. Dissolved oxygen (DO) values were measured at a distance of 60 cm from the MBG outlet. The final results of the study revealed that the higher the Q_Lvalue, the more frequent the intensity of bubble bursting, the greater the number of bubbles produced with the smaller diameter and the higher the DO value, and vice versa. Whereas the higher the Q_Gvalue, the intensity of the bubble breakdown that occurs is relatively the same, the number of bubbles produced is less and the diameter is larger and the DO value is lower, and vice versa.